Moral Spectatorship : Technologies of Voice and Affect in Postwar Representations of the Child - Cartwright, Lisa, 1959- (Book collections on Project MUSE., 2008)
Lisa Cartwright contributes to feminist film theory by developing a new psychoanalytic theory of spectatorship and human subjectivity.